Yellow sweet potato flour: Use in sweet bread processing to increase β-carotene content and improve quality - Nogueira A.C. (2018)
© 2018, Academia Brasileira de Ciencias. All rights reserved.Yellow sweet potato is mostly produced by small farmers, and may be a source of energy and carotenoids in the human diet, but it is a highly perishable crop. To increase its industrial application, yellow sweet potato flour has been produced for use in bakery products. This study aimed to evaluate the technological quality and the carotenoids content in sweet breads produced with the replacement of wheat flour by 0, 3, 6, and 9% yellow sweet potato flour. Breads were characterized by technological parameters and β-carotene levels during nine days of storage. Tukey’s test (p<0.05) was used for comparison between means. The increase in yellow sweet potato flour concentrations in bread led to a decrease of specific volume and firmness, and an increase in water activity, moisture, orange coloring, and carotenoids. During storage, the most significant changes were observed after the fifth day, with a decrease in intensity of the orange color. The β-carotene content was 0.1656 to 0.4715 μg/g in breads with yellow sweet potato flour. This work showed a novel use of yellow sweet potato in breads, which brings benefits to consumers’ health and for the agricultural business.